Ossification sequence heterochrony among amphibians. Issue 5 (20th September 2013) - Harrington, Sean M.; Harrison, Luke B.; Sheil, Christopher A.
SUMMARY Heterochrony is an important mechanism in the evolution of amphibians. Although studies have centered on the relationship between size and shape and the rates of development, ossification sequence heterochrony also may have been important. Rigorous, phylogenetic methods for assessing sequence heterochrony are relatively new, and a comprehensive study of the relative timing of ossification of skeletal elements has not been used to identify instances of sequence heterochrony across Amphibia. In this study, a new version of the program Parsimov‐based genetic inference (PGi) was used to identify shifts in ossification sequences across all extant orders of amphibians, for all major structural units of the skeleton. PGi identified a number of heterochronic sequence shifts in all analyses, the most interesting of which seem to be tied to differences in metamorphic patterns among major clades. Early ossification of the vomer, premaxilla, and dentary is retained by Apateon caducus and members of Gymnophiona and Urodela, which lack the strongly biphasic development seen in anurans. In contrast, bones associated with the jaws and face were identified as shifting late in the ancestor of Anura. The bones that do not shift late, and thereby occupy the earliest positions in the anuran cranial sequence, are those in regions of the skull that undergo the least restructuring throughout anuran metamorphosis. Additionally, within Anura, bones of the hind limb and pelvic girdle were also identified as shifting early in the sequence of ossification, which may be a result of functional constraints imposed by the drastic metamorphosis of most anurans.